Role of associating liver partition and portal vein ligation in staged hepatectomy (ALPPS)—strategy for colorectal liver metastases - Abbasi, Arezou; Rahnemai-Azar, Amir A.; Merath, Katiuscha; Weber, Sharon M.; Abbott, Daniel E.; Dillhoff, Mary; Cloyd, Jordan; Pawlik, Timothy M. (Translational Gastroenterology and Hepatology, 2018)
Colorectal carcinoma (CRC) is the third leading cause of cancer-related death in the United States. The liver is the most frequent site of metastasis and a key determinant of survival in patients with isolated colorectal liver metastasis (CRLM). Surgical resection remains the only hope for prolonged survival in patients with CRLM. However, most patients are deemed to be unresectable at presentation due to a small future liver remnant (FLR) and fear of post-hepatectomy liver failure. Procedures such as portal vein ligation or embolization (PVL/PVE) followed by hepatectomy have been established as standard methods to increase FLR volume, but have limitations dependent upon extent of disease and patient’s ability to grow the liver remnant. Recently, associating liver partition and portal vein ligation in staged hepatectomy (ALPPS) has been introduced as a technique to induce liver hypertrophy over a shorter time period. Being a complex two-stage surgical procedure, initial reports of higher ALPPS-associated complications and mortality limited its worldwide adoption by hepatobiliary surgeons. However, recent studies have showed ALPPS superiority over conventional procedures in terms of feasibility and inducing liver hypertrophy, with comparable morbidity and mortality. We herein review the role of ALPPS in management of patients with CRLM.